Comparing Eosinophilic Esophagitis in a Black and Non-Black Pediatric Cohort. Issue 4 (6th July 2022) - Edwards-Salmon, Sofia; Moraczewski, Jason; Offerle, Thomas; Sinclair, Elizabeth M.; Xiang, Yijin; Gillespie, Scott; Kruszewski, Patrice
Abstract : Objectives: To compare presenting symptoms, comorbidities, disease, and treatment characteristics of a black pediatric eosinophilic esophagitis (EoE) group to a non-black pediatric EoE group. Methods: A retrospective chart review consisting of pediatric patients diagnosed with EoE between the years of 2010 and 2018 at a single urban pediatric hospital system comprising 143 black pediatric patients compared with 142 non-black pediatric patients with similar distribution of age and sex. Results: Both groups were majority male, and the median age of diagnosis between the black and non-black group was 5.1 and 6.7 years old, respectively. Comorbidities more commonly seen in the black group included food allergies, atopic dermatitis, asthma, and allergic rhinitis. Black patients were more likely to present with failure to thrive (FTT)/poor growth, whereas non-black patients were more likely to present with abdominal pain. There was no statistically significant difference between the groups in achieving remission using current therapies. The black group had higher rates of nonadherence to medical therapies. Conclusions: This is the largest study to date comparing a black versus non-black pediatric EoE population. The black population had more atopic comorbidities and FTT at presentation and had significantly more issues with nonadherence. This new knowledge describing EoE in a minority population will hopefully improve awareness, diagnosis, and management of EoE in this population.